A STUDY ON BENEFITS OF EMPLOYEE RETENTION (Journal of Finance, Business and Management Studies, 2026)
Employee Retention is a critical factor in the long-term success of organizations. This study explores the numerous benefits of retaining skilled employees, focusing on areas such as cost reduction, productivity, and organizational culture. It highlights how retaining talent leads to decreased recruitment and training costs, as well as increased employee engagement and performance. Additionally, long-term employees contribute to the development of strong company culture, mentorship, and knowledge sharing, which boosts overall efficiency. The study also emphasizes the role of employee loyalty in enhancing customer satisfaction and organizational stability. The findings suggest that effective retention strategies, including competitive compensation, career development opportunities, and a positive work environment, are essential to achieving these benefits. Recommendations are provided for organizations looking to improve their retention practices and build a more resilient workforce.
Keywords: Employee Retention; Morale; Organizational culture; Productivity; Turnover; Employee Retention Benefits